Comorbidities Associated With Poor Outcomes Following Operative Hammertoe Correction in a Geriatric Population. Issue 4 (13th October 2020) - Maidman, Samuel D.; Nash, Amalie E.; Manz, Wesley J.; Spencer, Corey C.; Fantry, Amanda; Tenenbaum, Shay; Brodsky, James; Bariteau, Jason T.
Background: Although complications following hammertoe correction surgery are rare, older patients with comorbid conditions are often considered poorer operative candidates compared with younger, healthier patients because of a suspected increased risk of adverse outcomes. The aim of this study was to determine if the presence of multiple comorbidities was associated with increased complications or unsuccessful patient-reported outcomes following operative hammertoe correction in geriatric patients. Methods: Prospectively collected data was reviewed on 78 patients aged 60 years or older who underwent operative correction of hammertoe deformity. Patient demographics, comorbidities, and postoperative complications were recorded. Patient-reported outcomes were assessed using preoperative and postoperative visual analog scale for pain and Short Form Health Survey Physical and Mental Component Summary with 1 year of follow-up. Patients were divided into 2 groups based on number of comorbidities (0 or 1 vs > 2) and then compared. The average age of patients was 69.4 years and the prevalence of comorbidities in the study population was as follows: 11.5% smokers, 25.6% on blood thinners, 15.4% with rheumatoid arthritis, 7.7% with diabetes mellitus, 2.6% with peripheral arterial disease, 6.4% with chronic obstructive pulmonary disease, 11.5% with coronary artery disease, and 23.1% with osteoporosis. Results: Fifty-three patients (67.9%) had 0 or 1 comorbidity and 25 (32.1%) had 2 or more comorbidities. Compared to the 0 or 1 comorbidity group, the presence of multiple comorbidities was associated with an adjusted odds ratio (OR) for superficial wound infection of 4.18 ( P = .045) and deformity recurrence requiring surgery OR of 23.15 ( P = .032). Patient-reported outcomes were similar between comorbidity groups. Conclusions: This study further informs foot and ankle specialists to maintain increased surveillance for postoperative complications and unsuccessful outcomes in patients with multiple comorbidities. Although geriatric patients still report significant improvements in both pain and function, patients with underlying medical conditions should be counseled about their increased risks when pursuing operative hammertoe correction. Level of Evidence: Level III, retrospective comparative series.